2013
DOI: 10.1186/1743-422x-10-24
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection and differentiation of Rice black streaked dwarf virus (RBSDV) and Southern rice black streaked dwarf virus (SRBSDV) by duplex real time RT-PCR

Abstract: BackgroundThe diseases caused by Rice black streaked dwarf virus (RBSDV) and Southern rice black streaked dwarf virus (SRBSDV) have been occurring epidemically in China and southeastern Asia in recent years. A sensitive, reliable and quantitative method is required to detect and distinguish for RBSDV and SRBSDV in rice and vector insects.ResultsWe developed a sensitive and lineage-specific duplex real time RT-qPCR for detection of RBSDV and SRBSDV in a single or/and double infection in rice samples. The duplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…First, reference genes must show an expression level which is high enough to be quantified easily, or at least without difficulty, in applications, particularly RT-qPCR. To determine a practical threshold to evaluate the ease of quantification, distributions of FPKM values were investigated in 16 genes that have been practically used in RTqPCR as reference genes by researchers (Abiko et al, 2005;Benschop et al, 2007;Papdi et al, 2008;Streitner et al, 2008;Li et al, 2009;Li et al, 2010;Fontaine et al, 2012;Kudo et al, 2012;Zhang et al, 2013;Wang et al, 2014;Yin et al, 2014;Gonzalez-Cabanelas et al, 2015;Kamada-Nobusada et al, 2015;Patil et al, 2015;Zhai et al, 2015). In 15 of the 16 genes, the 25th percentile of the FPKM values was above 10; the exception was the Arabidopsis PPR gene, all of whose FPKM values were below 10 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…First, reference genes must show an expression level which is high enough to be quantified easily, or at least without difficulty, in applications, particularly RT-qPCR. To determine a practical threshold to evaluate the ease of quantification, distributions of FPKM values were investigated in 16 genes that have been practically used in RTqPCR as reference genes by researchers (Abiko et al, 2005;Benschop et al, 2007;Papdi et al, 2008;Streitner et al, 2008;Li et al, 2009;Li et al, 2010;Fontaine et al, 2012;Kudo et al, 2012;Zhang et al, 2013;Wang et al, 2014;Yin et al, 2014;Gonzalez-Cabanelas et al, 2015;Kamada-Nobusada et al, 2015;Patil et al, 2015;Zhai et al, 2015). In 15 of the 16 genes, the 25th percentile of the FPKM values was above 10; the exception was the Arabidopsis PPR gene, all of whose FPKM values were below 10 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Field surveys of peach viruses showed that some peach trees were infected with both ACLSV and CGRMV in China (unpublished data). Recently, three articles have reported plant virus detection using multiple RT-qPCR assays [7-9]. Therefore, we initiated this study to develop a method to determine the absolute copy numbers of ACLSV and CGRMV genomes in peach tissues, and to evaluate a duplex SYBR Green I-based RT-qPCR assay for the detection of ACLSV and CGRMV in a single reaction.…”
Section: Main Textmentioning
confidence: 99%
“…Both methods of RT-PCR have been widely used to detect viruses in plants and insect vectors (Lett et al, 2002;Varga and James, 2005;Zhang et al, 2010Zhang et al, , 2013bWatanabe and Bressan, 2013;Wang et al, 2014a,b). In the present study, we sought to quantify two viruses over time in the various organs of their respective vector and nonvector insects using quantitative RT-PCR (RT-qPCR) and conventional RT-PCR.…”
Section: Introductionmentioning
confidence: 98%